Chromosomal Abnormalities 2020
DOI: 10.5772/intechopen.91425
|View full text |Cite
|
Sign up to set email alerts
|

Current Cytogenetic Abnormalities in Acute Myeloid Leukemia

Abstract: Cytogenetic abnormalities are frequently reported in the literature describing the presence of chromosomal rearrangements in important cases of acute myeloid leukemia (AML); the rate can reach 50–60% of cases of AML. Cytogenetic abnormalities represent an important prognosis factor, their analysis is crucial for AML; cytogenetic study permits to classify prognostic groups and indicate the treatment strategy and helps to improve the outcome of these patients and to increase their chances of cure. Hundreds of un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…Among this data set, inv(16)(p13.1q22) is the most common, observed in between 4-5% of AML patients that receive cytogenetic work-ups(10, 11). CytoTerra identified 4/4 inv(16) rearrangements observed by cytogenetics in the study population (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among this data set, inv(16)(p13.1q22) is the most common, observed in between 4-5% of AML patients that receive cytogenetic work-ups(10, 11). CytoTerra identified 4/4 inv(16) rearrangements observed by cytogenetics in the study population (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…5A). The next most common class of inversions observed are related rearrangements involving the MECOM ( EVI1 ) locus(11). In this study, both cytogenetics and CytoTerra identified a single instance of an inv(3)(q21.3q26.1) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Other additional chromosome abnormalities seen in patients with inv. ( 16) include +8, del(7q), and/or + 21and +22 [41,42]. Acute Promyelocytic Leukemia (APML), is a subtype of AML with the recurrent abnormality t(15;17) (q24.1;q21.2).…”
Section: Acute Myeloid Leukemia (Aml)mentioning
confidence: 99%
“…FISH constitues a big step for studying somatic chromosomal mosaicism and molecular cytogenetic detection of chromosomal variations in interphase nuclei [6,7].…”
Section: Fluorescence In Situ Hybridization (Fish)mentioning
confidence: 99%
“…The first gene mutation described in 2005, JAK2-V617F, turned out to be the most important and most frequently recurring somatic mutation in MPN [6][7][8][9]. The frequency ofJAK2-V617F is around 95% in PV and between 50% and 60% in ET and PMF [41].…”
Section: Meyloproliferative Neoplasm (Mpn)mentioning
confidence: 99%